La organización de la economía en una sociedad comunista: sobre la teoría de los tres momentos en Marx y algunas perspectivas contemporáneas - Sotomayor Trelles, José Enrique (Pontificia Universidad Católica del Perú, 2024)
This paper has two aims. First, it attempts to sketch what one may call the “theory of the three moments”—a theory concerning the transition to communism—in Karl Marx’s works: seizure of power through democratic means, progressive destruction of the mechanisms of class domination, and organization of a new society of free and associated producers. The second aim of this paper returns to the horizon of possibilities regarding the organization of economy in a society where the remains of the capitalist mode of production have been destroyed. Concerning this point, the relevant passages of Marx’s work are neither abundant nor detailed. However, some of them focus on the perspectives of the cooperative organization of the Paris Commune. Going beyond Marx, the paper also reviews some contemporary approaches that take up the path towards an emancipated future.

El presente artículo tiene dos objetivos: el primero consiste en delinear lo que podríamos llamar “teoría de los tres momentos” sobre la transición al comunismo en la obra de Karl Marx: toma del poder a través de medios democráticos, destrucción progresiva de los mecanismos de dominación de clase y organización de una nueva sociedad de productores libres y asociados. Por otra parte, el segundo objetivo del artículo retoma el horizonte de posibilidades de la organización de la economía en una sociedad donde se ha destruido los rezagos del modo de producción capitalista. En este extremo los pasajes de Marx no son abundantes ni detallados, aunque algunos de ellos se centran en las perspectivas de la organización cooperativa de la Comuna de París. Más allá de Marx, se pasará revista por algunas propuestas contemporáneas que retoman la senda de un futuro emancipado.
The Organization of Economy Within a Communist Society: On Marx’s Theory of the Three Moments and Some Contemporary Perspectives
Keywords: Communism; Karl Marx; Mode of production; Communist economy; Economic planning; Comunismo; Karl Marx; Modo de producción; Economía comunista; Planificación económica; https://purl.org/pe-repo/ocde/ford#6.03.01